Plant Growth Regulators to Decrease Wheat Height in High Fertility Scenarios - F. D. Spolidorio; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2019)
Lodging is a common concern in wheat production, and its intensity depends on many factors including the straw strength of the variety, nitrogen (N) levels, and plant growth regulator (PGR). However, there are limited data exploring how current Kansas wheat varieties respond to PGR applications at different fertility levels. Thus, our objective was to assess the effects of PGR on wheat varieties exposed to different levels of N fertilization. A field trial was established in a split-split-plot design and four replications in two Kansas locations (Great Bend and Ashland Bottoms) during the 2017–18 growing season. Factors evaluated were two N levels as whole plots (e.g., for a yield goal of 55 versus 73 bu/a), two varieties as sub-plot (below average straw strength with 1863 and above average straw strength with WB-Grainfield), and PGR (control versus 14.4 fl oz/a of Palisade applied at jointing). Due to an extremely dry growing season, biomass production was decreased and no lodging was observed. Still, the application of PGR decreased plant height at both locations by 0.6–1 inch, although this decrease depended on fertility level at the Great Bend site. WB-Grainfield was typically taller than 1863, regardless of location evaluated. Despite its effect of reducing plant height, grain yield was unaffected by PGR application. In Great Bend, grain yield was only affected by variety; while an interaction of variety × fertility affected grain yield in Ashland Bottoms. These results are promising as there was no yield drag from PGR applications despite an extremely dry growing season.
Keywords: wheat; growth regulator; variety; fertility; nitrogen